Design of Simple Harmonic Motion (SHM) devices based on IR obstacle sensors. Issue 1 (April 2021) - Setya, W; Fariha, D N; Handayani, W; Syafe`i, A
Abstract: The development of science and technology is inseparable from the availability of hardware and software. One of its uses is teaching aids in physics practicum, especially simple harmonic motion. Digital technology can shorten the time in the implementation of practical work in the field. In this study aims to design a simple harmonic motion practicum tool using Arduino Uno based on IR resistance sensors. Data was collected using a small angle of 10° with variations in the number of waves and time obtained. The results will be displayed on the LCD. This study also compares the results of recording digitally and manually. Based on the data obtained, the results of digital experiments are more accurate than the results of manual experiments with an accuracy of 96.69% and digital SHM device experiments also show precise results. So that digital SHM tools can be performed on physics experiments in simple harmonic motion material.